Implementasi Pembelajaran PAI Menggunakan Metode Talaqqi dan Musyafahah dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa - Aziz, Mursal; Hairullah; Irma Yanti Sitorus (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to describe the implementation of the Talaqqi and Musyafahah methods in Islamic Religious Education (PAI) learning at MIS Islamiyah Kuala Beringin. The type of this research method is descriptive qualitative research with a case study approach. The subjects of the study were PAI teachers at MIS Islamiyah Kuala Beringin. The data collection method used interviews, observations and documentation. The data analysis technique used Miles and Huberman with data reduction techniques, data presentation and drawing conclusions. The results of this study indicate that there are still many students at MIS Islamiyah Kuala Beringin who have not fully mastered how to read the Qur'an correctly according to the rules of tajwid. The use of talaqqi and musyafahah methods in learning to read the Al-Qur'an has proven to be better in helping students quickly and easily master reading skills according to the rules of tajwid law. Increasing students' abilities includes the ability to pronounce letters according to the correct makhraj, recognizing the properties of letters, as well as other skills that support better reading of the Al-Qur'an. Keywords: Implementation, Reading the Koran, PAI, Talaqqi and Musyafahah